Leaky Feeder as A VoIP Transmission Medium - Martono Dwi Atmadja; Farida Arinie Soelistianto; Harrij Mukti Kristiana; Argo Indrianto (Westscience Press, 2024)
VoIP (Voice over Internet Protocol) is a technology that allows its user to transmit voices using an internet network, although the technology uses the internet as its transmission medium VoIP still uses cable for most of its applications resulting in complicated cable management if not managed properly, this method can be optimized via wireless transmission for more efficient mobility and system configuration. This research aims to find out the capabilities of Leaky Feeder cable as a medium for VoIP transmission. A leaky feeder system consists of a single cable that runs along its designated space. This cable has gaps that allow the radio signal to leak into or out of the cable along its entire length meaning it can cover a larger area than the usual point-to-point transmission using cable. The parameters observed in particular are Signal Strength, Bit Rate, Packet Loss, Delay, and Throughput, the data obtained is taken quantitatively and its average value is calculated to ensure the system efficiency. Signal Strength trial shows an average value of -60.25 dBm, while also having an uplink and downlink of each 14.86 Mbps and 12.79 Mbps, Bit Rate trial shows that the more clients are served the less bandwidth each client will have , The Packet Loss trial shows an outstanding 0.71% loss, the delay trial shows an average of 20.5ms delay with -40dbm signal quality, and finally Throughput trial shows the highest value at 388Kbps when performing one call with -65dbm signal quality . This shows that the application of Leaky Feeder cable use on VoIP transmission is in a good category. Using Leaky Feeders in buildings can also reduce the number of Access Point installations required to cover the same area.